Understanding Moral Weakness - Thero, Daniel P., (Brill Book Archive Part 1, ISBN: 9789004472495., 2006)
This book considers the common human predicament that we often choose an action other than the one we perceive to be best. Philosophers know this problem as akrasia. The author develops a nuanced understanding of the nature and causes of akrasia by integrating the best insights of Socrates, Aristotle, Augustine, and Aquinas, and several contemporary philosophers.